Spinning, oxidative damage and hemolysis in athletes - Gallo, Giuseppe; Martino, Guglielmo; Carino, Annarita (Free Radicals and Antioxidants)
Background: The aim of this study is to put into evidence and verify the correlation between hemolysis and oxidative damage in subjects who practice spinning. Methods: A total of 12 volunteers, aged 35 5 years were enrolled in the present study (60 min) before and (60 min) after practicing spinning. The measurement of lipid peroxidation products and the he- molysis assays conducted on blood samples of athletic subjects, and also the red blood cell morphological study. Results: The obtained data evidence that there are significant differences at least 60 min after training: in malonyldialdehyde value (0.12 0.05 nmol/ml) and in malonyldialdehyde value with 2,20-azobis (2-ami- dinopropane) dihydrochloride (0.22 0.05 nmol/ml), in hemolysis data up to both 80 min (oxidative lysis) and 120 min (2,20 azobis (2-amidinopropane) dihydrochloride lysis) confirmed by microscopical analysis. Conclusion: The described data on red blood cell hemolysis, after exercise-induced oxidative damage (malonyldialdehyde), and the degradation kinetic under action of 2,20-azobis (2-amidinopropane) dihydrochloride can be described according to a multistage process with multiple contemporaneous equilibria. The final red blood cell echinocytic form could describe the end product of process. Conse- quently authors hypothesize a relationship between spinning exercise, plasma membrane oxidation and hemolysis susceptibility.
Keywords: Hemolysis; Oxidative damage; Spinning; MDA